Investigation on meso-debonding process of the sandstone–concrete interface induced by freeze–thaw cycles using NMR technology. (20th August 2020) - Shen, Yanjun; Wang, Yongzhi; Wei, Xin; Jia, Hailiang; Yan, Ruixin
Highlights: Effect of freeze–thaw on sandstone–concrete interfacial debonding was measured. Debond process of sandstone–concrete interface was investigated by NMR SE-SPI. Determine the interface-influencing zone(IIZ) under freeze–thaw cycles using NMR SE-SPI. The debonding occurs in the sandstone near the interface under freeze–thaw cycles. Abstract: Sufficient bonding at concrete–rock interfaces is an important prerequisite when designing supports using concrete or shotcrete. However, the bonding between concrete and rock is often affected by low temperatures in cold regions. This study focuses on the effects that freeze–thaw cycles have on meso-debonding at sandstone–concrete interfaces. The prepared sandstone-concretes composite materials were subjected to freeze–thaw cycles and nuclear magnetic resonance (NMR) test. The effects of the freeze–thaw cycles on sandstone–concrete composites and the interfacial pore changes are discussed in this paper. The extent of the interface-influencing zone (IIZ) and the process controlling interface debonding are described based on the results of those experiments. The three primary conclusions are as follows: (1) The volume of the micropores and macropores in sandstone increases with the freeze–thaw cycles; however, the volume of the mesopores decreases. (2) The IIZ lies in the sandstone, near the interface, and is accompanied by water enrichment. (3) From a mesoscopic point of view, the process of debonding in the sandstone-concrete is not initialized at the interface but occurs in the sandstone near the interface.